Hipertensão arterial sistêmica na população adulta brasileira e fatores associados - Marinho, Patrícia de Menezes (2017)
Systemic arterial hypertension (SAH) is currently considered an important global public health problem, with a high impact on the quality of life of individuals and in the economic sector. Data from the World Health Organization and studies conducted in several countries show that the number of hypertensive adults has increased worldwide, with 1.13 billion cases estimated in 2015. In this context, considering the complexity and multicausality of this disease affecting different strata of the population, it is important to investigate the associated factors with its development in the brazilian adult population, since knowledge of the magnitude of the problem is essential for the development of actions aimed for control of the disease. In view of this, a literature review chapter and an original article were prepared. The review chapter addresses the prevalence of SAH, with emphasis on those obtained from data from national and international health surveys, the main associated factors, and the political strategies adopted by the brazilian government and the public power of different countries to coping the disease in question. The original article aimed to estimate the prevalence of SAH and its associated factors in the brazilian adult population. This is a cross-sectional study involving brazilian adults aged 18 years or older, using data obtained from the National Health Survey conducted in 2013. The analysis of prevalence and associated factors with hypertension includes aspects sociodemographic, behavioral and comorbidities. Poisson regression was performed, with crude and adjusted prevalence ratios calculated for each exposure variable. It was verified that the prevalence of SAH increased with age in both sexes, being greater in males. The final explanatory model indicated that male gender, advanced age, not living with a partner and low education level remained as associated factors with SAH in the study population. Regarding the behavioral aspects, we observed a greater chance of hypertension in physically inactive individuals and with a smoking habit. Regarding comorbidities, the variables remaining overweight, diabetes type 2 and high blood cholesterol remained in the final model. These findings reinforce the need for measures based on strategies for prevention and control of the disease and its predictors, which contribute to reduce the burden of the said disease and its complications, still present in a significant form in the country.